Effects of the Addition of Different Additives before Mechanical Separation of Pig Slurry on Composition and Gaseous Emissions - José L. S. Pereira; Adelaide Perdigão; Ana Tavares; Maria E. F. Silva; Isabel Brás; Dulcineia F. Wessel (Agronomy, 2022)
The treatment of animal slurry is used to improve management on a farm scale. The aim of this laboratory study was to assess the effects of the addition of the additives biochar, alum and clinoptilolite before the mechanical separation of whole pig slurry (WS) on the characteristics and emission of NH3, N2O, CO2 and CH4 from solid (SF) and liquid fractions (LF). The additives were mixed with WS (5% w/w), followed by separation, in a total of 12 treatments with 3 replicates, including the controls and WS with additives. Gaseous emissions were measured for 30 d by a photoacoustic multigas monitor, and initial characteristics of the slurries were assessed. The results indicated that the separation of the WS modified the initial physicochemical characteristics and increased the GWP emissions of the SF and LF, but not the NH3 losses. However, the addition of additives before separation increased the nutrient value and reduced the GWP emissions from the SF and LF. Additionally, just the additive alum was effective in the reduction of E. coli. The additives led to significant reductions in NH3 and N2O emissions, with higher reductions in NH3 losses for alum (51% for NH3) and similar N2O losses for all additives (70% for N2O) observed, whereas the CO2 and CH4 emissions were reduced by biochar (25% for CO2 and 50% for CH4) and alum (33% for CO2 and 30% for CH4) but not by clinoptilolite. Although the additives had a positive effect on slurry management, it can be concluded that the addition of alum before mechanical separation has the potential to be the best mitigation measure because it improves the nutrient content and sanitation and decreases gaseous losses from slurry management.